Artificial Intelligence in Education: An Overview - Saiful Latif; Zulkifli Ahmad (EDUKASI, 2025)
Artificial intelligence is rapidly transforming various sectors, and education is no exception, with the potential to revolutionize teaching, learning, and administration. The development of AI in recent years has opened up many opportunities for education. AI offers the potential to transform teaching approaches by developing more engaging and responsive learning environments, potentially enhancing traditional educational strategies. AI is revolutionizing education by enhancing learning experiences, changing teaching methodologies, and optimizing administrative. AI-based personalized learning systems analyze student data to create a customized learning experience for each student, allowing them to learn more efficiently using less time and resources than traditional teaching methods. The integration of AI in education presents significant challenges and considerations that must be addressed to ensure ethical, equitable, and effective implementation.